Altering the time of vaccination against respiratory pathogens to enhance antibody response and performance of feeder cattle - Lippolis, K. D.; Cooke, R. F. [UNESP]; Schubach, K. M.; Brandao, A. P. [UNESP]; Silva, L. G. T. da [UNESP]; Marques, R. S.; Bohnert, D. W. (Amer Soc Animal Science, 2016)
Ninety Angus × Hereford calves were ranked by sex, BW, and age and assigned to 1 of 3 vaccination schemes against the bovine respiratory disease complex: 1) vaccination at weaning (d 0) and a booster at feedlot entry (d 30; CON; n = 30), 2) vaccination 15 d before weaning (d −15) and a booster 15 d before feedlot entry (d 15; EARLY; n = 30), and 3) vaccination 15 d after weaning (d 15) and a booster 15 d after feedlot entry (d 45; DELAYED; n = 30). From d −15 to 7, calves were maintained as a single group on pasture. On d 8, calves were placed into 1 of 18 drylot pens (6 pens/treatment; 5 calves/pen) and fed alfalfa–triticale hay. On d 29, calves were transported 1,440 km in a livestock trailer and unloaded on d 30 at the same feed yard with the same pen arrangement used prior to transport. From d 30 to 75, calves were fed a receiving diet based on alfalfa–triticale hay + corn-based concentrate. Calf BW was recorded on 2 consecutive days (d −15, −14, 0, 1, 28, 29, 75, and 76). Blood samples were collected on d −15, 0, 15, 30, 45, 60, and 75. The EARLY calves had less (P ≤ 0.09) ADG before weaning (d −15 to −1); however, they had greater (P ≤ 0.01) ADG during feedlot receiving (d 30 to 75) compared with calves with the other treatments. During preconditioning (d 0 to 29), CON calves had greater (P ≤ 0.04) DMI compared with EARLY and DELAYED calves. During feedlot receiving, no treatment differences were detected (P ≥ 0.17) for hay or concentrate DMI, G:F, and morbidity and mortality rates. There were no treatment effects on calf BW at weaning and at the end of the preconditioning or receiving periods (P ≥ 0.65). Plasma concentrations of antibodies against Mannheimia haemolytica were greater (P ≤ 0.05) in EARLY calves than in CON and DELAYED calves on d 0, greater (P ≤ 0.04) for CON calves than for EARLY and DELAYED calves on d 15, greater (P ≤ 0.02) in DELAYED and EARLY calves than in CON calves on d 30, and greater (P = 0.03) in EARLY calves than in CON calves on d 75. Plasma concentrations of antibodies against bovine viral diarrhea viruses were greater (P ≤ 0.04) in EARLY calves than in CON and DELAYED calves on d 15 and greater for EARLY and CON calves than for DELAYED calves on d 30 and 45. Collectively, EARLY calves had greater plasma concentrations of antibodies against the evaluated pathogens at feedlot entry and increased ADG during receiving compared with their CON and DELAYED cohorts. Hence, anticipating initial and booster vaccinations against respiratory pathogens to provide both doses prior to feedlot entry appears to be a valid strategy to enhance cattle health and performance during feedlot receiving.
Keywords: Feeder cattle; Health; Performance; Respiratory diseases; Vaccination